Baby Care Products, Health And Hygiene Concerns- Learning For Marketers Post Covid 19 - Aswathy.R, Dr. K.S. Chandrasekar (International Journal of Advanced Science and Technology, 2020)
Baby care market is one of the fastest growing segments in the country. The rapid growth witnessed in the baby care market can be attributed to factors such as improvements in the demographics and change in consumption style of Indian consumer (Bindhu & Prasad, 2017, Chandrasekar & Aswathy, 2019). Products that are meant for meeting the needs of children in the age group 0-4 years are considered under the baby care product category. Baby and child-specific products Market in Indian is expected to grow at a CAGR of 8% with sales set to reach INR29.4 billion in 202l as per the report by Euromonitor International May, 2017. The out beak of COVID 19 has challenged the global market in a multidimensional way, and India is not an exception. The unexpected and sudden attack of the epidemic left the marketers and consumers with little preparations to manage the emergency. In the back drop of COVID 19, this paper attempts to address some of the major issues related to baby care product consumption pattern, health and hygiene factors and the learnings a marketer can imbibe to revive their future strategies.